1983
DOI: 10.1113/jphysiol.1983.sp014772
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of nasal heat exchange in resting reindeer.

Abstract: SUMMARY1. Total respiratory heat loss (t.r.h.l.) in resting reindeer has been calculated from exhaled air temperature (Te) and respiratory minute volume (T) obtained during heat and cold stress in both summer and winter.2. Exhaled air temperature decreased with decreasing ambient temperature (Ta)in both summer and winter. The lowest T; recorded was +6 0C at a Ta of -45 0C in winter and the highest + 38 0C at a T. of + 29 0C in summer. At any T., Te was higher in winter than in summer. v was constant with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 9 publications
2
39
0
Order By: Relevance
“…Blix and Johnsen (1983) found that, at any given ambient temperature, the temperature of air expired by the reindeer is consistently lower in summer (when fur insulation is low) than in winter (when it is high). This implies that the animal is capable of adjusting the efficiency of the nasal heat exchange to maintain thermal balance along with the great seasonal changes in body insulation ( Fig.…”
Section: Physiological Defencesmentioning
confidence: 98%
See 2 more Smart Citations
“…Blix and Johnsen (1983) found that, at any given ambient temperature, the temperature of air expired by the reindeer is consistently lower in summer (when fur insulation is low) than in winter (when it is high). This implies that the animal is capable of adjusting the efficiency of the nasal heat exchange to maintain thermal balance along with the great seasonal changes in body insulation ( Fig.…”
Section: Physiological Defencesmentioning
confidence: 98%
“…Here, the nasal surfaces have developed into a highly convoluted mass, reminiscent of a car radiator, with an air space of <1 mm between the lamellae . This structure allows ∼65% of the heat and ∼80% of the water added to the inspired air to be regained on expiration at an ambient temperature of −25°C in both reindeer and seals (Blix and Johnsen, 1983;Blix, 1987, 1989).…”
Section: Physiological Defencesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when the animal is in a state of extreme heat dissipation (in a hot environment, or during running), respiratory minute volume will increase substantially (Blix and Johnsen, 1983). However, an increase in respiratory minute volume without circulatory adjustments, will result in a substantial decrease of nasal mucosal temperature and a subsequent reduction in expired air temperature, which would compromise the dissipation of heat bv way of the respiratory tract.…”
mentioning
confidence: 97%
“…This mode of heat conservation, which is based on cooling of the expired air, and thereby condensation of water, particularly at low ambient temperatures, is possible because of the existence of a temperature gradient along the length of the nasal passages (Johnsen et ai, 1985a). Furthermore, Blix and Johnsen (1983) have shown that there is a summer to winter difference of about 12°C in exhaled air temperature at, for instance, -10°C ambient temperature, in these animals. At this ambient temperature respiratory minute volume and frequency were the same in summer and winter.…”
mentioning
confidence: 99%